PERIDINIOPSIS CUNNINGTONII LEMMERM. – НОВИЙ ДЛЯ ЧОРНОГО МОРЯ ВИД ДІНОФЛАГЕЛЛАТ (DINOFLAGELLATA) - Крахмальний, О. Ф. (Marine Ecological Journal, 2023)
Description and pictures of the new dinoflagellates for the Black Sea Peridiniopsis cunningtonii Lemmerm. (Dinoflagellata) are given. This species was found in the plankton of the Odessa Gulf in the summer, 2008. The comparison of this species and the morphologically similar Peridinium quadridens (F.Stein) Bourr. was carried out.